2017
DOI: 10.1111/trf.14122
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of platelet antibodies using a sensitive multiplex assay system–platelet antibody bead array

Abstract: The PABA is a rapid, highly sensitive and specific, multiplex bead-based assay for detecting human platelet antibodies. Such a simple yet high-throughput platform will facilitate practical, routine testing for the identification of platelet-specific antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…[1620] Thus, HPA-3a would appear to be significantly immunogenic factor only less than HPA-1a and HPA-5b. With the development of technology, numerous new approaches provide highly sensitive and specific, multiplex bead-based assay for detecting human platelet antibodies, [2123] which can contribute to a high diagnostic rate of the NAIT.…”
Section: Discussionmentioning
confidence: 99%
“…[1620] Thus, HPA-3a would appear to be significantly immunogenic factor only less than HPA-1a and HPA-5b. With the development of technology, numerous new approaches provide highly sensitive and specific, multiplex bead-based assay for detecting human platelet antibodies, [2123] which can contribute to a high diagnostic rate of the NAIT.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest antibodies were specific for dexamethasone and leucovorin in patient 1 and irinotecan in patient 2. In a platelet antibody bead array assay, 11 it was found that dexamethasone-and leucovorin-dependent antibodies from patient 1 and the irinotecan-dependent antibody from patient 2 recognized a IIb /b 3 integrin (GPIIb/IIIa) and the oxaliplatindependent antibody from patient 1 recognized GPIb/IX (supplemental Figure 1, available on the Blood Web site). Other DDAb targets were not identified.…”
Section: Patient 2 (mentioning
confidence: 99%
“…Detection and identification of platelet‐reactive antibodies was performed at the Platelet & Neutrophil Immunology International Reference Lab, BloodCenter of Wisconsin (BCW), Milwaukee using both a flow cytometry test with intact target platelets, and a highly sensitive and specific Platelet Antibody Bead Array (PABA) for detection and identification of platelet specific antibodies against human platelet alloantigens (HPA). Flow cytometry testing was performed as previously described .…”
Section: Description Of Case/case Reportmentioning
confidence: 99%
“…Beads were washed 3 times and incubated with fluorescent anti‐human IgG (Jackson ImmunoResearch Labs, West Grove, PA) for detection of patient HPA antibodies. Bead fluorescence intensity was measured on a Luminex 200 (Luminex Corporation) and results determined using an in‐house developed software program to call HPA antibody specificity …”
Section: Description Of Case/case Reportmentioning
confidence: 99%